2015
DOI: 10.4103/0971-3026.155857
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in endometrial carcinoma

Abstract: Endometrial carcinoma (EC) is the most common gynecologic malignancy in the United States. Prognosis depends on patient age, histological grade, depth of myometrial invasion and/or cervical invasion, and the presence of lymph node metastases. Although EC is staged surgically according to the International Federation of Gynecology and Obstetrics (FIGO) system, preoperative imaging can assist in optimal treatment planning. Several imaging techniques such as transvaginal ultrasonography (TVUS), computed tomograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 59 publications
1
48
1
3
Order By: Relevance
“…As one of the extensively-applied cell proliferation markers, Ki-67 can reflect the proliferation degree of malignant cells and is associated with the progression, metastasis and prognosis of various malignancies. A lot of studies have shown that that the prognosis of patients with EC is closely related to the age, histological grade, depth of myometrial invasion and/or cervical invasion, and the presence of lymph node metastases (Faria et al, 2015;Takahashi et al, 2015), and some biological indicators including hormone receptors, oncogenes and tumor suppressor genes are also involved (Ito et al, 1997), but these indicators are short of comprehensive verification of clinical trials with large sample sizes. Hence, in this study, the expression of ER, PR, C-erbB-2 and Ki-67 in EC tissue was detected using immunohistochemical SP method and their relationships with the clinicopathological features of EC were also investigated so as to provide valuable indicators for the clinical treatment and prognostic evaluation of EC.…”
Section: Expression Of Er Pr C-erbb-2 and Ki-67 In Endometrial Carcmentioning
confidence: 99%
“…As one of the extensively-applied cell proliferation markers, Ki-67 can reflect the proliferation degree of malignant cells and is associated with the progression, metastasis and prognosis of various malignancies. A lot of studies have shown that that the prognosis of patients with EC is closely related to the age, histological grade, depth of myometrial invasion and/or cervical invasion, and the presence of lymph node metastases (Faria et al, 2015;Takahashi et al, 2015), and some biological indicators including hormone receptors, oncogenes and tumor suppressor genes are also involved (Ito et al, 1997), but these indicators are short of comprehensive verification of clinical trials with large sample sizes. Hence, in this study, the expression of ER, PR, C-erbB-2 and Ki-67 in EC tissue was detected using immunohistochemical SP method and their relationships with the clinicopathological features of EC were also investigated so as to provide valuable indicators for the clinical treatment and prognostic evaluation of EC.…”
Section: Expression Of Er Pr C-erbb-2 and Ki-67 In Endometrial Carcmentioning
confidence: 99%
“…Endometrial cancer is diagnosed mainly during the 6th and 7th decades. 3 The 10-year survival rate is 75%, because 75-80% of women present with symptoms of postmenopausal bleeding at an early stage. 4 The risk factors associated with the development of endometrial cancer include obesity, nulliparity unopposed estrogen intake, Stein-Leventhal syndrome, diabetes mellitus, Lynch syndrome, and tamoxifen therapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, vigorous debate has challenged the use of anatomic assessments solely relying on tumor morphologic information, not taking into account functional tumor characteristics that may prove highly relevant for the clinical phenotype (11)(12)(13). In this regard, to better understand the tumor microenvironment, metabolic PET tracers such as 18 F-FDG, in combination with CT, can overcome the limitations of morphologic imaging alone, because functional changes possible to detect by 18 F-FDG PET/CT often precede morphologic changes detectable by conventional MRI or CT (14,15).…”
mentioning
confidence: 99%